#### Answer

4 ft by 6 ft

#### Work Step by Step

$x*(x+2)=24$
$x^2+2x=24$
$x^2+2x-24=24-24$
$x^2+2x-24=0$
$(x+6)(x-4)=0$
$x+6 = 0$
$x+6-6 = 0-6$
$x = -6$
$x-4=0$
$x-4+4 =0+4$
$x = 4$
We can't have a negative length, so $x\ne-6$

Published by
Prentice Hall

ISBN 10:
0133500403

ISBN 13:
978-0-13350-040-0

4 ft by 6 ft

You can help us out by revising, improving and updating this answer.

Update this answerAfter you claim an answer you’ll have **24 hours** to send in a draft. An editor
will review the submission and either publish your submission or provide feedback.